Discourse transparency and the meaning of temporal locating adverbs - Altshuler, D (Springer Nature, 2013)
This paper proposes that a core semantic property of temporal locating adverbs is the ability (or the lack thereof) to introduce a new time discourse referent. The core data comes from that same day in narrative discourse. I argue that unlike other previously studied temporal locating adverbs—which introduce a new time discourse referent and relate it to the speech time or a salient time introduced into the discourse context—that same day is ‘twice anaphoric’, i.e. it retrieves two salient times from the input context without introducing one of its own. Moreover, I argue that the adverb currently is like that same day in not introducing a new time discourse referent. Unlike that same day, however, currently has both a deictic and an anaphoric usage analogous to on Sunday. The analysis that I propose is implemented within Compositional Discourse Representation Theory. It illustrates how adverbial meaning can be integrated within a more general theory of temporal interpretation.